Hungarian Monitoring, 21 May 1990 . [Magyar rádiófigyelő], 1990. május 21 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Elections in Romania - Polish railways strike - The 3rd millionth Trabant car is produced - Dubček meeting with Gorbachev - Iliescu wins the Romanian elections Domestic Affairs: - Committee hearing of the new ministers - The Hungarian Social Democratic Party (MSZDP) warned Anna Petrasovics to resign Economy: - Workers' protest in the Óbuda shipyard - Jewish tombs damaged in Sopron - Domestic civil aviation recommences in Hungary Külpolitika: - Választások Romániában - Lengyel vasutassztrájk - Elkészült a hárommilliomodik Trabant - Dubček Gorbacsovval tárgyalt - Iliescu nyeri a romániai választásokat Belpolitika: - Új miniszterek bizottsági meghallgatásai - MSZDP felszólítja Petrasovitsot a lemondásra Gazdaság: - Az Óbudai Hajógyárban munkások tüntetnek - Zsidó sírok megrongálása Sopronban - Magyarországon megindul a belföldi légi forgalom